Synthesis and use of caged sphingolipids - Scott, RH; Pollock, J; Ayar, A; Thatcher, NM; Zehavi, U (Elsevier Academic Press Inc, 2000)
[Abstract Not Available]
Keywords: Enzymatic Glycosphingolipid Synthesis; Sphingosine 1-Phosphate; Flash-Photolysis; Polymer Supports; Kinase; Dihydrosphingosine; Mobilization; Currents; Release; Calcium